Paratubal cyst torsion. Case report - Rondón Tapia, Marta (2017)
Paratubal cysts are simple cystic structures filled with serous fluid that are located along the Fallopian tube, usually arising from the broad ligament or mesosalpinx. It is important to always consider tube torsion as a differential diagnosis for female patients presenting with an acute abdomen, and to be aware of the need for quick diagnosis and surgical treatment in order to preserve the patient’s fertility, especially in younger patients of child-bearing age. We present the case of a 16 year-old female patient who complained of intense hypogastric pain together with vomits. During laparoscopy, a torted paratubal cyst was found in the right adnexa. Laparotomy was performed to remove the cyst and salpingectomy was carried out, since the right Fallopian tube was unsalvageable. Histological analysis showed that the mass was a paratubal cyst.